[18F]FDG PET/CT detection and therapeutic response assessment of primary multisystem extranodal diffuse large B-cell lymphoma without lymph node involvement: a case report - Liao, Taiping; Deng, Huan; Long, Yongjun; He, Jun; Li, Lingxiao; Xiao, Cong; Li, Jun (Frontiers in Oncology, 2025)
IntroductionPrimary extranodal diffuse large B-cell lymphoma (PE-DLBCL) originates in extranodal organs and accounts for approximately 30%–40% of all DLBCL cases. PE-DLBCL involving multiple organs without lymph node involvement is uncommon. We present a case of DLBCL in a patient who initially presented with abdominal pain. Abdominal computed tomography (CT) revealed suspicious neoplastic lesions in the liver and ileum. Histopathological examination of an ileal biopsy confirmed the diagnosis of DLBCL. The patient subsequently underwent [18F]FDG PET/CT for disease staging. PET/CT demonstrated multiple hypermetabolic lesions in the liver, right kidney, and ileum, notably in the absence of any lymph node involvement throughout the body. After four cycles of R-CHOP (rituximab, cyclophosphamide, doxorubicin, vincristine, and prednisone) chemotherapy, [18F]FDG PET/CT evaluation revealed significant shrinkage of the abdominal lesions, indicating a favorable prognosis.ConclusionThis case demonstrates a rare presentation of multisystem PE-DLBCL without lymphadenopathy and underscores the vital role of [18F]FDG PET/CT in identifying disease extent and guiding accurate staging and management, as well as evaluating treatment response.